A Mini Review on Nanocarbon-Based 1D Macroscopic Fibers: Assembly Strategies and Mechanical Properties - Kou, Liang; Liu, Yingjun; Zhang, Cheng; Shao, Le; Tian, Zhanyuan; Deng, Zengshe; Gao, Chao (Nano-Micro Letters, 2017)
Nanocarbon-based materials, such as carbon nanotubes (CNTs) and graphene have been attached much attention by scientific and industrial community. As two representative nanocarbon materials, one-dimensional CNTs and two-dimensional graphene both possess remarkable mechanical properties. In the past years, a large amount of work have been done by using CNTs or graphene as building blocks for constructing novel, macroscopic, mechanically strong fibrous materials. In this review, we summarize the assembly approaches of CNT-based fibers and graphene-based fibers in chronological order, respectively. The mechanical performances of these fibrous materials are compared, and the critical influences on the mechanical properties are discussed. Personal perspectives on the fabrication methods of CNT- and graphene-based fibers are further presented.